(untitled) (College of Basic Education Research Journal, 2026)
The current research aims to identify the level of intellectual pollution among students of the College of Basic Education in general, and the significance of statistical differences in intellectual pollution among students of the College of Basic Education in the level of intellectual pollution according to the specialization variable (scientific-human), the grade variable (second-fourth), and the gender variable (males-females). In order to achieve the research objectives, the researcher adopted the intellectual pollution scale prepared by (Al-Ubaidi, 2021) consisting of (30) paragraphs with four alternatives (applies to Always, often applies to me, sometimes applies to me, does not apply to me), with four weights (1, 2, 3, 4), which was applied to a sample of (96) male and female students from the scientific and humanities departments. After distributing the scale to experts and arbitrators as in Appendix (2), the apparent validity of the scale was extracted and it obtained an agreement rate of (90%), which is a high agreement rate. The stability was extracted using the test-retest method, with a period of (13) days between the first application and the second application. A stability rate of (80%) was obtained, and then the scale was applied to the basic sample of (96) and the data were processed statistically using the t-test for one sample (t-test) and the t-test For two independent samples (t-test) the results showed the presence of a significant difference in the level of intellectual pollution among students of the College of Basic Education, and the absence of a significant difference between females and males in the level of intellectual pollution, the presence of a significant difference in the level of intellectual pollution according to the stage variable (second and fourth), and the absence of a statistically significant difference in the level of intellectual pollution according to the specialization variable (scientific-human) at a significance level of (0.05)In light of the results, the researcher reached some recommendations and proposals, which we will present later in the fifth chapter, including: - Peaceful coexistence among the different segments of society, instilling loyalty to the family, society and country, and conducting a similar study on intellectual pollution with middle school student.